MINAT BELAJAR AKSARA LOKAL SASAMBO MAHASISWA PGSD UNIVERSITAS MATARAM - Arif Widodo; Dyah Indraswati; Setiani Novitasari; Nursaptini Nursaptini; Aisa Nikmah Rahmatih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Local scripts are the priceless cultural heritage of the nation. The existence of local scripts today is increasingly eroded by the use of Latin writing. A few young people are able to write local scripts. One of the forgotten local scripts is the Sasambo script in West Nusa Tenggara (NTB). This study aims to describe the learning interest of PGSD students on local scripts. This research was designed in a quantitative descriptive form. The data was collected through surveys. The instrument used were a closed questionnaire and interview guidelines. Data analysis used descriptive statistics. The subject of research was PGSD students of University of Mataram. The results showed that PGSD students' interest in learning about local scripts was very low. The indicators showed that few students have ever learned local scripts, the number of students interested in learning local scripts was small, the number of students who were willing to read literature was small, the number of students who had interested on local scripts was small, the use of local scripts was also small and the assumption that local scripts were not important to learn. The reason for the lack of interest in learning about local scripts was because local scripts were difficult to learn and were not needed anymore in practical life. Based on the findings, it needs various efforts to increase student interest in learning local scripts Sasambo through learning innovation. By learning local scripts, it is expected that the preservation of local scripts will be maintained.